Cyphellostereum indicum (Hygrophoraceae), a new species of basidiolichen from India - Nayaka, Sanjeeva; Debnath, Ambikesh (Phytotaxa, 2023)
Cyphellostereum indicum, an interesting basidiolichen is described as a new species. The species was collected from Arunachal Pradesh, an Indian state located within the Eastern Himalayas. The species is characterized by a terricolous habitat, the cyanobacteria Rhizonema as the photobiont that is loosely wrapped by fungus hyphae, white to cream-coloured, flabellate, solitary hymenophores, and thin-walled, smooth, simple, irregular to pip-shaped basidiospores 3.18–4.9 × 2.06–2.9 μm. The phylogenetic analysis clearly shows its position in a separate branch within the genus Cyphellostereum making it a species distinct from any previously reported species. Cyphellostereum indicum is the third basidiolichen reported from India.